1985
DOI: 10.1159/000163327
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of B Cell Development and Antibody Responses in Mice with Polyclonal Rabbit and Monoclonal Rat Anti-IgM Antibodies

Abstract: Mice treated from birth with polyclonal, crude or affinity purified rabbit or monoclonal rat anti-mouse IgM antibodies [b-7-6 and C-2-23: Eur. J. Immunol. 14:753–757, 1984] were found to be heavily suppressed with respect to B-cell activities. Crude or affinity purified rabbit or monoclonal rat anti-mouse IgM gave comparable results as follows: (1) serum IgM was below detectable levels; (2) serum IgG was reduced to about 1–3% of normal levels; (3) free anti-IgM was always detectable; (4) IgM and/or Ò¡-light-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Female DBA/2, BALB/c, ICR, (B10.D2 X C57BL/10)F| or C57BL/6 mice were obtained from the Institut für Zuchthygiene, Abteilung Labortier kunde, Tierspital Zürich (Switzerland); they were used at the age of 7-15 weeks. B cell-deprived mice were raised exactly as described [8,10].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Female DBA/2, BALB/c, ICR, (B10.D2 X C57BL/10)F| or C57BL/6 mice were obtained from the Institut für Zuchthygiene, Abteilung Labortier kunde, Tierspital Zürich (Switzerland); they were used at the age of 7-15 weeks. B cell-deprived mice were raised exactly as described [8,10].…”
Section: Methodsmentioning
confidence: 99%
“…VSV induces an early T cell-independent B cell response in mice [6][7][8] which around day 6-8 is switched to a T cell-dependent IgG response [7,9], The present study set out to characterize the dose-response parameters of the neutralizing antibody response to live, UV-inactivated VSV or purified VSV glyco protein G in mice. We found that priming of mice with vesicular stomatitis virus (VSV) required doses greater than 10-100 plaque forming units (pfu) of virus.…”
Section: Introductionmentioning
confidence: 99%